(untitled) - Fabrice Hatem (New York, 1998)
The book reviews medium-term trends in foreign direct investment around the world as seen by 300 managers of transnational corporations and international experts. It analyzes the impact of recent economic developments, most notably by Asian crisis, and looks at how United States, European and Asian corporations are expanding their international presence.
Keywords: investments, foreign